2022
DOI: 10.3390/medicina58081078
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Aspects of Aging in Venous Thromboembolism: An Update

Abstract: The aim of this review is to highlight all the factors that associate venous thromboembolism (VTE) with aging. Elderly people are characterized by a higher incidence of thrombosis taking into account the co-existing comorbidities, complications and fatality that arise. Based on the Virchow triad, pathophysiological aspects of venous stasis, endothelium injury and hypercoagulability in elderly people (≥65 years) are described in detail. More precisely, venous wall structure, nitric oxide (NO) and endothelin-1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 145 publications
0
10
0
Order By: Relevance
“…In combination with previous studies claiming that testosterone levels in men reach their highest level at approximately 30 years of age and then gradually decrease at a rate of 1% to 2% per year ( Herring et al, 2013 ). Age is an acquired thrombogenic factor that is closely associated with pathological and physiological changes ( Akrivou et al, 2022 ). Biased correlation analysis after controlling for age suggested that as testosterone decreased in men with diabetes, K values decreased and Angle, MA values, and CL values increased.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with previous studies claiming that testosterone levels in men reach their highest level at approximately 30 years of age and then gradually decrease at a rate of 1% to 2% per year ( Herring et al, 2013 ). Age is an acquired thrombogenic factor that is closely associated with pathological and physiological changes ( Akrivou et al, 2022 ). Biased correlation analysis after controlling for age suggested that as testosterone decreased in men with diabetes, K values decreased and Angle, MA values, and CL values increased.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of a nationwide Swedish registry denoted a skewed distribution for VTE with respect to advancing age [11]. Analysis of the cohorts in the Cardiovascular Health Study and the Atherosclerosis Risk in Communities study revealed an 8% remaining lifetime risk of VTE in adults aged 45-64 years [12] with risk and incidence rates for VTE increasing significantly in subsequent decades [13][14][15][16]. While these distributions clearly demonstrate which age groups bear the major burden of VTE [11,16,17], etiology is not unifactorial.…”
Section: Epidemiology Of Venous Thromboembolismmentioning
confidence: 99%
“…Analysis of the cohorts in the Cardiovascular Health Study and the Atherosclerosis Risk in Communities study revealed an 8% remaining lifetime risk of VTE in adults aged 45-64 years [12] with risk and incidence rates for VTE increasing significantly in subsequent decades [13][14][15][16]. While these distributions clearly demonstrate which age groups bear the major burden of VTE [11,16,17], etiology is not unifactorial. Multiple risk factors are often identified in patients presenting with VTE in the clinic.…”
Section: Epidemiology Of Venous Thromboembolismmentioning
confidence: 99%
“…CVI is common among geriatric patients due to structural changes that occur in venous valves and walls with age, and CVI has been associated with a three-fold elevated risk of venous thrombosis and pulmonary embolism [ 130 ]. Treating venous thromboembolism in geriatric patients is complex since they have a higher likelihood of thrombosis and bleeding.…”
Section: Reviewmentioning
confidence: 99%
“…Treating venous thromboembolism in geriatric patients is complex since they have a higher likelihood of thrombosis and bleeding. Thus, if there are no contraindications, anticoagulant therapy may be prescribed [ 130 , 131 ].…”
Section: Reviewmentioning
confidence: 99%